(untitled) (Journal of Hama University, 2025)
The research aimed to reveal the attitudes of teachers of the second cycle of basic education towards blended education in Lattakia city, and to know the differences in the estimates of the members of the research sample about their attitudes towards blended education according to the variables (academic qualification, years of experience), and used the descriptive approach. The sample included (204) teachers and teachers of the second cycle of basic education in Lattakia city. To achieve the objective of the research, a questionnaire was designed consisting of (50) phrases. The results of the research showed that the attitudes of teachers in the schools of the second cycle of basic education in the city of Lattakia towards the application of blended education are high, and the results showed that there are no statistically significant differences in the estimates of the research sample members of the teachers of the second cycle of basic education about their attitudes towards blended education according to the variable of the number of years of experience, and there are statistically significant differences in the estimates of the members of the research sample according to the variable of scientific qualification in favor of holders of the educational qualification diploma. The research made many proposals, the most important of which are: emphasizing the importance of applying blended learning in the educational process, and conducting another research on teachers’ attitudes towards blended learning in another educational stage, from different perspectives.